La Revue Syndicaliste et Coopérative (Paris: M. Rivière)
"Periodiciteit: maandelijksHoofdredactie: A. ThomasRedactie: E. Rottach, C. Mutschler, L. Varlez, J. H. Ricard, E. Pouget, A. Quist, H. Brotherton, L. Troclet Beheer: L. Gervaise (le gérant)Drukker/Drukkerij: Impr. Coopérative Ouvrière, Villeneuve-St-Georges"